Search for R-parity violating production of single sneutrinos in e+e- collisions at √s = 189-209 GeV: The ALEPH collaboration - Heister,A; Schael,S; Barate,R; Brunelière,R; de,Bonis I; Decamp,D; Goy,C; Jezequel,S; Lees,JP; Martin,F; Merle,E; Minard,MN; et al. (European Physical Journal C, 2002)
A search for single sneutrino production under the assumption that R-parity is violated via a single dominant LL coupling is presented. This search considers the process eγ → ν and is performed using the data collected by the ALEPH detector at centre-of-mass energies from 189 GeV up to 209 GeV corresponding to an integrated luminosity of 637.1 pb-1. The numbers of observed candidate events are in agreement with Standard Model expectations and 95% confidence level upper limits on five of the LL couplings are given as a function of the assumed sneutrino mass.